An examination of youth protective factors and caregiver parenting skills at entry into the child welfare system and their association with justice system involvement. (April 2019) - Summersett, Faith C.; Jordan, Neil; Griffin, Gene; Kisiel, Cassandra; Goldenthal, Hayley; Martinovich, Zoran
Abstract: This study sought to distinguish youth in the child welfare system who became involved with the justice system from youth who did not become involved with the justice system based on the youth's protective factors and their caregivers' parenting skills. This was accomplished by examining the frequency of specific youth protective factors and their caregivers' parenting skills. It was also accomplished by examining the differences in the total number of youth protective factors and the total number of their caregivers' parenting skills at entry into the child welfare system based on justice system involvement. We also sought to describe the demographic characteristics of youth protective factors and caregiver parenting skills. Using chi-square and analysis of variance (ANOVA) tests, study findings indicated that while the majority of children did not become justice involved, of those kids who did become justice involved, the majority of them were minority youth. There was also a higher proportion of youth with identified child-specific protective factors at baseline without later justice involvement compared to the proportion of youth who later became involved with the justice system. In addition, youth with a higher number of protective factors and caregiver parenting skills at baseline did not have future involvement with the justice system compared to youth with a lower number of protective factors and caregiver parenting skills. Lastly, in terms of parenting practices, the most notable demographic differences were related to race/ethnicity. Findings indicated that the biological parents and caregivers of White youth had more parenting skills compared to the biological parents and caregivers of minority youth. One of the implications of these findings is that reducing dual involvement for youth in the child welfare system may be achieved through strength building and providing additional services to youth and families at the beginning of the youth's care in the child welfare system.